Eco-ELT: Transforming English Language Teaching through Sustainable and Innovative Materials - Kalsum; Humaeroah; Agussalim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study investigates the integration of Eco-English Language Teaching (Eco-ELT) within the English study program curriculum through the ADDIE instructional design model. The primary objective is to develop and evaluate English teaching materials that enhance both language proficiency and environmental awareness among students. Employing a qualitative research approach, the study follows the ADDIE model's five phases: Analysis, Design, Development, Implementation, and Evaluation. Data were collected via observations, interviews, and document analysis to assess the effectiveness of the Eco-ELT materials. Findings reveal that incorporating Eco-ELT significantly improves students' engagement, English language skills, and environmental consciousness. The study also highlights challenges, such as the need for comprehensive teacher training and resource constraints. The research underscores Eco-ELT as a promising approach for integrating environmental education into language teaching, with implications for English teaching material development and further exploration of sustainable educational practices.